(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The aim of this research is to understand the complexity of student’s and teaching staff behavior and experience in times when study work in real auditoriums is mixed with remote learning. Since 2020, the author has conducted an annual survey of several hundred students of computer science at the University of Latvia and Riga Technical University for 5 years about the possibilities, usefulness, problems, satisfaction, benefits and visions of remote and distance learning. The study shows the dynamics of changes in student opinions and technical capabilities over these 5 years, including COVID and post-COVID periods. The author offers a model of productive study work that includes mixed methods, Moodle e-course management and advanced technologies, increasing student responsibility in remote work in an environment where some technical problems and artificial intelligence are present, to achieve the best possible result.